Phylogenetic Analysis of the Aglaonema Putative MYB Gene for Anthocyanin Regulation in Plants (Biosaintifika: Journal of Biology & Biology Education, 2026)
The red colour in Aglaonema leaves is influenced by anthocyanin accumulation, which is synthesized through a series of reactions catalyzed by specific enzymes. These proteins are encoded by genes regulated by transcription factors, among which the MYB gene family plays a vital role. The research aimed to identify a putative MYB gene in Aglaonema that encodes an MYB-transcription factor and analyze its relationship with several previously reported MYB genes involved in anthocyanin regulation. We aligned six gene sequences from Araceae and used a highly conserved region among five sequences to design the AMYB primer. Phylogenetic analysis of the Aglaonema putative MYB gene (amplified by the AMYB primer) and three previously characterized MYB genes from other plant species revealed that the AMYB primer was successfully constructed with optimal properties. The Aglaonema putative MYB gene sequence shares the highest similarity with HvMYB, known to activate HvMYC2 – a gene strongly associated with anthocyanin expression in plants, highlighted by a bootstrap value of 97% and a genetic distance of 0.3. The findings provide a reference for primer design and gene identification in Aglaonema, contributing valuable data for genetic conservation and plant breeding programs. This research supports the Sustainable Development Goals of Good Health and Well-Being (number 3) and Life on Land (number 15). Aglaonema plants, developed to produce unique leaf color patterns, can improve farmers' economic well-being and, in turn, enhance their overall well-being. Furthermore, Aglaonema development can enrich ornamental germplasm collections, thereby contributing to increased biodiversity in Indonesia.